Screen-Printing Electrochemical Architectures - Banks, Craig E.; Foster, Christopher W.; Kadara, Rashid O.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
.
Introduction and current applications of screen-printed electrochemical architectures -- Fundamentals of screen-printing electrochemical architectures -- Fabricating screen-printed electrochemical architectures: successful design and fabrication -- Quality Control/Quality analysis of electrochemical screen-printed sensors. .
Keywords: Chemistry, Technical; Electronic circuits; Optical materials; Electric power production; Energy storage; Industrial Chemistry; Electronic Circuits and Systems; Optical Materials; Electrical Power Engineering; Mechanical Power Engineering; Mechanical and Thermal Energy Storage